Comparative in vivo study of alloy titanium implants with two different surfaces: biomechanical and SEM analysis - Souza, Francisley Avila [UNESP]; Mata Furtado, Thayane Silveira; Campos Dayube, Ulisses Ribeiro; Melo, Willian Moraes [UNESP]; Nishioka, Renato Sussumu [UNESP]; Poli, Pier Paolo; Maiorana, Carlo; Perri de Carvalho, Paulo Sergio [UNESP] (Springer, 2019)
Objectives The purpose of this study was to evaluate the biomechanical behavior of the interface formed between bone and implants with machined surfaces (MS) and those modified by Al2O3 sandblasting and acid etching (SBAS). Materials and methods Before surgery, topographic characterization was performed by SEM-EDX and by mean roughness measurements. Ten Albinus rabbits received randomly 20 Ti-6Al-4V implants on its right and left tibiae, with one implant placed in each tibia. After implant insertion, the implant stability quotient (ISQ) was measured by means of resonance frequency analysis (RFA). After 3 and 6 weeks, the ISQ was again measured, followed by torque removal measurements. Analysis of variance and Tukey tests were used to analyze the data. The surface of the implants removed was evaluated by SEM-EDX. Immunohistochemical analysis of osteopontin (OPN) and osteocalcin (OC) protein was performed in bone tissue. Results The topographic characterization showed differences between the analyzed surfaces, and the mean roughness values of SBAS group were statistically higher than MS. Overall, higher statistically significant ISQ values were observed in the SBAS group compared to the MS group (p = 0.012). The intra-group comparison of ISQ values in the SBAS group showed statistically significant differences between 0 and 3 weeks (p = 0.032) and 0 and 6 weeks (p = 0.003). The torque removal measurements of group SBAS were statistically higher when compared with the torque removal measurements of group MS in the time intervals of 3 weeks (p = 0.002) and 6 weeks (p < 0.001). SEM-EDX of the implant surfaces removed in SBAS group showed greater bone tissue covering and mean values atomic in percentage of Ca, P, and O statistically superior (p < 0.05) than MS group. Immunohistochemical reactions showed intense OC immunolabeling at 6 weeks postoperative for SBAS group. Conclusions The topographical modifications made in group SBAS allowed a better mechanical interlocking between the implant and bone tissue.
Keywords: Biomechanics; Dental implant; Osseointegration; Surface modification